NEUROENDOCRINE DIFFERENTIATED BREAST CARCINOMA: A CASE REPORT - Mücteba Gündüz; Yalın İşcan; Yeşim Erbil; Mahmut Müslümanoğlu (European Journal of Breast Health, 2009)

(untitled)
Neuroendocrine tumors are rarely seen in the breast. They are commonly located in the gastrointestinal tract and the lungs. These tumors of the breast may be purely neuroendocrine or neuroendocrine diff erentiated. Some breast tumors may have neuroendocrine foci. The clinical signifi cance of these tumors are unclear. However, they are thought to have no relation with the prognosis and patient outcome. This is the report of a patient with neuroendocrine diff erentiated invasive breast carcinoma treated surgically in the classical manner.